A novel method improving the temperature uniformity of hot-plate under induction heating. (January 2021) - Jin, Wang; Xing, Chen; Lu, Yu; Baoshou, Sun; Li, Dequn
In the paper, a novel method to improve the uniformity of the temperature distribution on the surface of the hot-plate is presented. Firstly, the effect of magnetic flux density under coupling of the electromagnetic and heat transfer on target surface temperature is studied numerically by using the commercial simulation software COMSOL Multiphysics. To evaluate the uniformity of the temperature distribution on the target surface, the temperature nonuniformity index on the target surface was firstly employed in terms of a specific designed electric coil. Secondly, the principal components analysis combined with the orthogonal test method is employed to analyze the shape parameters and obtain optimized temperature distribution at the target surface of the hot-plate. The simulated results show that the uniformity of temperature can be greatly improved by appropriately adjusting distribution of magnetic flux and the uniform temperature distribution can be achieved on a heating surface of 130 mm in length, 130 mm in width, and 30 mm in height. Finally, the optimizations of target surface temperature on hot-plate with different target temperatures were studied as well.